2014
DOI: 10.14400/jdc.2014.12.10.391
|View full text |Cite
|
Sign up to set email alerts
|

A Predictive Model of Health Promotion Behavior in Nursing Students

Abstract: This study seeks to carry out a literary review of preceding studies and the health improvement model of Pender(1987) on university students majoring in nursing to explain the health improvement behaviors and identify the factors that affect their activities to provide a framework for developing a more effective nursing mediation method that promotes health improvement behaviors. The study subjects were 204 university students majoring in nursing who have had clinical practice experience. The period for data c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 7 publications
1
5
0
Order By: Relevance
“…This implies that the subjective perception of health is an important variable affecting health behaviors. In addition, a higher level of self-esteem resulted in a higher level of health promotion behaviors, which was also consistent with the findings of previous studies [ 13 , 14 ]. College students with higher self-esteem were shown to have lower stress levels and a positive attitude towards their life, and they thus performed health promotion behaviors appropriately.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This implies that the subjective perception of health is an important variable affecting health behaviors. In addition, a higher level of self-esteem resulted in a higher level of health promotion behaviors, which was also consistent with the findings of previous studies [ 13 , 14 ]. College students with higher self-esteem were shown to have lower stress levels and a positive attitude towards their life, and they thus performed health promotion behaviors appropriately.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, health perception-a subjective process of how health-related issues are understood-is presented as a variable affecting health promotion behaviors [ 7 ]. There are also several socio-psychological variables including socio-psychological health [ 10 ], self-efficacy, perceived benefit and disability, health status and importance [ 13 ], self-esteem, and social support [ 14 ]. Among these, low self-esteem contributes to disease, as low self-esteem decreases belief in the ability to influence one’s environment and situation, which in turn affects health promotion behaviors [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, many studies are being conducted to analyze the factors affecting the health promotion behaviors of nursing students in order to enhance their health promotion efforts [ 13 ]. Variables affecting health promotion behaviors included marital status [ 4 ]; perceived disability, perceived self-efficacy, perceived social support, clinical practice stress [ 13 ]; and family function and health perceptions [ 14 ]. However, no strategies have been identified that can be used to effectively improve the health-promoting behaviors of nursing students.…”
Section: Introductionmentioning
confidence: 99%
“…After social support, self-efficacy had the greatest influence on health promotion behavior, and the higher the self-efficacy, the better the health promotion behavior. Studies on nurses [37] and nursing students [38] have also reported similar results, confirming that self-efficacy is a major factor that promotes health promotion behavior. A study on the factors affecting health promotion behavior among shift workers [20] reported that those who received health-related education exhibited high self-efficacy.…”
Section: Discussionmentioning
confidence: 52%